2000
DOI: 10.1038/eye.2000.11
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification cataract surgery: is routine review necessary on the first post-operative day?

Abstract: Purpose To determine the value of routine review on the first post-operative day following phacoemulsification cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 12 publications
1
49
0
1
Order By: Relevance
“…During the transition of cataract surgery from extracapsular cataract extraction to phacoemulsification, it was noted that the day-1 postoperative intervention rate after routine phacoemulsification was around 3% and this was deemed sufficiently low to justify the omission of the day-1 visit. [18][19][20] Allan et al 18 suggest that if the intervention rate is o5%, the visit is probably unnecessary, apart from the mutual reassurance for the patient and the surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the transition of cataract surgery from extracapsular cataract extraction to phacoemulsification, it was noted that the day-1 postoperative intervention rate after routine phacoemulsification was around 3% and this was deemed sufficiently low to justify the omission of the day-1 visit. [18][19][20] Allan et al 18 suggest that if the intervention rate is o5%, the visit is probably unnecessary, apart from the mutual reassurance for the patient and the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, the IOP spike after VR surgery can persistent for at least 2 weeks. 15 It remains unclear whether a raised IOP for a short period is damaging, in the absence of pre-existing glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It has been suggested that the 1-day postoperative intraocular pressure (IOP) check post routine uncomplicated phacoemulsification can be abandoned for a number of reasons. 1,[4][5][6][7] Some of these include the fact that new surgical complications are unlikely to be picked up on the first day, peak IOP may have already passed, economical constraints, improved postoperative outcomes and low complication rates. 1,4 However in patients with glaucoma or ocular hypertension (OHT), either this approach was not advocated, or it was recommended that prophylactic regimes against a raised IOP should be followed as investigated in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have reported an early increase in IOP following phacoemulsification. [5][6][7] The amount of this increase is related to several factors including the type of the viscoelastic agent and different surgical techniques.…”
mentioning
confidence: 99%